Heme-Oxygenase-1 Expression Contributes to the Immunoregulation Induced by Fasciola hepatica and Promotes Infection - Carasi, Paula; Rodríguez, Ernesto; da Costa, Valeria; Frigerio, Sofía; Brossard, Natalie; Noya, Verónica; Robello, Carlos; Anegón, Ignacio; Freire, Teresa (Frontiers in Immunology, 2017)
Fasciola hepatica, also known as the liver fluke, is a trematode that infects livestock and humans causing fasciolosis, a zoonotic disease of increasing importance due to its worldwide distribution and high economic losses. This parasite immunoregulates the host immune system by inducing a strong Th2 and regulatory T immune response by immunomodulating dendritic cell (DC) maturation and alternative activation of macrophages. In this paper we show that F. hepatica infection in mice induces the upregulation of heme-oxygenase-1 (HO-1), the rate-limiting enzyme in the catabolism of free heme that regulates the host inflammatory response. We show and characterize two different populations of antigen presenting cells that express HO-1 during infection in the peritoneum of infected animals. Cells that expressed high levels of HO-1 expressed intermediate levels of F4/80 but high expression of CD11c, CD38, TGFβ and IL-10 suggesting that they correspond to regulatory DCs. On the other hand, cells expressing intermediate levels of HO-1 expressed high levels of F4/80, CD68, Ly6C and FIZZ-1 indicating that they might correspond to alternatively activated macrophages. Furthermore, the pharmacological induction of HO-1 with the synthetic metalloporphyrin CoPP promoted F. hepatica infection increasing the clinical signs associated with the disease. In contrast, treatment with the HO-1 inhibitor SnPP protected mice from parasite infection, indicating that HO-1 plays an essential role during F. hepatica infection. Finally, HO-1 expression during F. hepatica infection was associated with TGFβ and IL-10 levels in liver and peritoneum, suggesting that HO-1 controls the expression of these immunoregulatory cytokines during infection favoring parasite survival in the host. These results contribute to the elucidation of the immunoregulatory mechanisms induced by F. hepatica in the host and provide alternative checkpoints to control fasciolosis.